Analisis Pajak Penghasilan atas Transaksi E-Commerce di Kabupaten Gresik - Emma Rosalinawati; Syaiful Syaiful (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2018)
Taxes on online transactions become one of the expansion of tax revenues which presents a challenge for the taxation system in Indonesia. Basically the obligation of taxpayers of conventional businesses and online businesses (e-commerce) is no different. Gresik is one of the regencies in the East Java region where people like to make buying and selling transactions online. The study uses a normative and empirical approach in Gresik Regency which is applied by conducting library studies and field studies through data collection from the results of interviews that will be conducted to; e-commerce players from Gresik Regency, Tax Practitioners Tax Service Office (KPP) North Gresik and academics who master taxation. The results of interviews with e-commerce actors obtained information that most e-commerce actors did not agree with the imposition of tax collection on transactions on e-commerce transactions. The head of the extensification and extension section at the Gresik North Tax Service Office revealed that the potential of online business transactions in Gresik is growing very rapidly but the limited data available so far the North Gresik Tax Office has not been able to distinguish the payment of taxes on e-transactions commerce and conventional.